Implementasi Multimedia Development Life Cycle Pada Aplikasi Pembelajaran Multimedia Interaktif Algoritma dan Pemrograman Dasar Untuk Mahasiswa Berkebutuhan Khusus Berbasis Android - Shidqie Alisyafiq; Bella Hardiyana; Rani Puspita Dhaniawaty (Jurnal Pendidikan Kebutuhan Khusus, 2021)
The purpose of building a Multimedia Application for Interactive Learning Algorithms and Basic Programming is expected to create a new atmosphere in the lecture process so that students with special needs become more active and lecturers do not have obstacles in visualizing the material. The choice of interactive multimedia as a learning medium is to complement and support elements such as material objectives, methods, and assessment tools that exist in the conventional teaching and learning process. In conducting this research, the researcher used the Multimedia Development Life Cycle (MDLC) approach which consisted of six stages, namely conceptualization, design, material collection, manufacture, testing, and distribution. The subjects of this study were students with special needs in the Information Systems Study Program at the Indonesian Computer University (Unikom). The result of this research is a learning application as a tool for lecturers in delivering Algorithm and Basic Programming material so as to create a new atmosphere in the classroom and it is hoped that lectures will be more effective for students with special needs.